2020
DOI: 10.1016/j.jvoice.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Laryngeal Signs and Symptoms, Acoustic Measures, and Quality of Life in Finnish Primary and Kindergarten School Teachers

Abstract: Objective This study investigated the relationship between the acoustic measure smoothed cepstral peak prominence (CPPS), teacher's quality of life as measured by the voice activity and participation profile (VAPP), laryngeal signs and symptoms, voice related health problems and laryngoscopic findings in Finnish teachers. The relationship between CPPS and sound pressure level (SPL) was also assessed. Methods Vowel and text samples from 183 healthy Finnish teachers (99 kindergarten teachers [KT] and 84 primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…1,3,16,69 CPPS was determined for each tone using the 'To PowerCepstrogram' function, following the method reported in Watts et al, 3 and used by others. 1,16,19 It is important to note that the 'Peak search pitch range (Hz)' was increased from 60 to 330 Hz (standard) to 60 to 1000 Hz to accommodate the f o of all generated tones in Conditions 1.1 and 1.2. PRAAT has two available methods for determining CPPS, however the newer method used here has proven to be robust and is simpler in implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,16,69 CPPS was determined for each tone using the 'To PowerCepstrogram' function, following the method reported in Watts et al, 3 and used by others. 1,16,19 It is important to note that the 'Peak search pitch range (Hz)' was increased from 60 to 330 Hz (standard) to 60 to 1000 Hz to accommodate the f o of all generated tones in Conditions 1.1 and 1.2. PRAAT has two available methods for determining CPPS, however the newer method used here has proven to be robust and is simpler in implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that CPPS improved with increased SPL values. 15,17,19,20 In these studies, voice samples were taken from spoken passages and elicited and sustained vowel conditions, all within habitual speech range and at various levels of intensity.…”
Section: Vibrato Extent and Cppsmentioning
confidence: 99%
“…Although numerous studies have shown the strong relationship between dysphonia and CPP 3,[7][8][9][10][11][12][13][14][15][16] , significant external factors unrelated to dysphonia may also influence CPP. These factors include patient-controlled factors (such as prosodic changes in loudness or fundamental frequency [17][18][19][20][21][22][23][24] ), recording environment or microphone used 25,26 , stimuli type (sustained vowel, continuous speech), and phonemes present in stimuli 17,[27][28][29][30][31][32][33] , as well as the program used to calculate CPP values 9,10,15,24,26,27,[34][35][36] . Therefore, it is essential that clinicians using CPP reduce as many of these external factors as possible when comparing across patients or within the same patient across time points (i.e., before and after therapy).…”
Section: Introductionmentioning
confidence: 99%
“…Systemically addressing occupational vocal health is advocated for the 25–33% of global labour forces who are vocally reliant to undertake work-related activity and participation (Buckley et al in press; Palheta Neto et al, 2009 ; Titze et al, 1997 ; Vilkman, 2001 , 2004 ). Reliance on voice for workability increases workers’ risks of poor vocal health (Buckley et al, 2015 ; Fuentes-López et al, 2019 ; Morawska & Niebudek-Bogusz, 2017 ; Munier et al, 2019 ; Rezende et al, 2020 ; Titze et al, 1997 ; Verdolini & Ramig, 2001 ). In overall terms, poor vocal health also negatively affects vocally reliant workers’ health and well-being.…”
Section: Introductionmentioning
confidence: 99%